TARI TRADISIONAL DALAM RANAH TARI POPULER: KONTRIBUSI, RELEVANSI, DAN KEBERLANJUTAN BUDAYA - Indrayuda, Indrayuda (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
Recent development of dance performance is not only esthetical and artistic; it has improved farther along with social cultural changes and economic development, which is supported by the scientific and technological changes that have encouraged the improvement of the art and knowledge about dances. In choreographic learning in academic environment, the arrangement pattern in choreography is not limited to the conventional that the consequence of movement, but also a media for criticism and expression of the artists. Currently dance does not belong to certain tradition of a community but to individuals. The individual belonging of the dance is widely known as popular dance, both monumental and contemporary dance. In Indonesia, both monumental and contemporary popular dances tend not to be detached from their traditional idiom or spirit in their cultural choreographic background, even all of their arrangement source stems from traditional kinesthetic dance. This phenomenon becomes a new trend in dance creation and dance choreographic learning in Indonesia, many of which are developed by art academicians, art studios and workshops.